Statistical Cluster Points of Subsequences of Double Sequences - Miller, Harry I. (Sarajevo Journal of Mathematics, 2024)
The main result of this paper is the double sequence analogue of a theorem about cluster points of single sequences that has recently submitted for publication [8]. Namely, we show here that if $x$ is a double sequence then $Γ_x$ (the set of statistical cluster points of $x$) equals $Γ_y$ (the set of statistical cluster points of $y$) for "almost all" subsequences $y$ of $x.$